Роль макро- та мікроелементів у патогенезі цукрового діабету 2-го типу - Суслик, Г. І.; Капустинська, О. С.; Гирявенко, О. Я. (Clinical Endocrinology and Endocrine Surgery, 2014)
This review presents and analyzes the results of clinical researches dedicated to the role of macro- and microelements in the pathogenesis of insulin resistance in type 2 diabetes mellitus and also to micro- and macroangiopathies. There has been made a conclusion that diabetes mellitus is an ehlementozah, in other words a pathological condition with an imbalance of essential macro- and microelements. Mg2 +, Zn2 + and Cr deficiency in blood initiates the development and progression of insulin resistance and impairment of blood rheology. Deficiency of Mn, Se and excess of Cu provoke strengthening of peroxidation processes and contribute to the development of late complications of diabetes mellitus.